2002
DOI: 10.1038/416403a
|View full text |Cite
|
Sign up to set email alerts
|

Amino acids from ultraviolet irradiation of interstellar ice analogues

Abstract: Amino acids are the essential molecular components of living organisms on Earth, but the proposed mechanisms for their spontaneous generation have been unable to account for their presence in Earth's early history. The delivery of extraterrestrial organic compounds has been proposed as an alternative to generation on Earth, and some amino acids have been found in several meteorites. Here we report the detection of amino acids in the room-temperature residue of an interstellar ice analogue that was ultraviolet-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
314
3
5

Year Published

2002
2002
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 739 publications
(328 citation statements)
references
References 24 publications
6
314
3
5
Order By: Relevance
“…Without hydrolysis, meteoritic amino acids are less abundant. These results can be correlated with the analysis of refractory residues obtained after the VUV irradiation and the warming of ice analogs (Bernstein et al 2002;Muñoz-Caro et al 2002). Without hydrolysis, amino acids are not identified, whereas amino acids are present after the residue hydrolysis (Nuevo et al 2008).…”
Section: Introductionsupporting
confidence: 56%
“…Without hydrolysis, meteoritic amino acids are less abundant. These results can be correlated with the analysis of refractory residues obtained after the VUV irradiation and the warming of ice analogs (Bernstein et al 2002;Muñoz-Caro et al 2002). Without hydrolysis, amino acids are not identified, whereas amino acids are present after the residue hydrolysis (Nuevo et al 2008).…”
Section: Introductionsupporting
confidence: 56%
“…In this context, experimental simulations in laboratory have shown that a large quantity of amino acids can be formed by simple vacuum ultraviolet (VUV) irradiation of interstellar ice analogs. These abiotic syntheses of amino acids only lead, without asymmetric induction, to the formation of racemic mixtures (Bernstein et al 2002;Muñoz-Caro et al 2002). In meteorites such as Murchison or Murray, amino acids have been detected (Cronin et al 1980).…”
Section: A Model For Asymmetric Amino Acid Photolysismentioning
confidence: 99%
“…The first step is thus to compare these data with astronomical observations in order to identify the importance of photochemical processes in astrophysical environments. After sample heating, radicals and molecules can rearrange to form a residue which includes complex organic molecules such as amino acids, detected after hydrolysis treatment of the samples (Bernstein et al, 2002;Muñoz-Caro et al, 2002;Nuevo et al, 2008). Without this treatment only very few amounts of amino acids are detected (Nuevo et al, 2008).…”
Section: Surfaces As Concentration Agents In Chemical Evolutionmentioning
confidence: 99%
See 2 more Smart Citations